Detailed kinetic mechanism for the hydrogen production via the oxidative reforming of ethanol. (29th June 2021) - Pio, Gianmaria; Ruocco, Concetta; Palma, Vincenzo; Salzano, Ernesto
Highlights: Experimental study of catalyst deactivation and apparent kinetics for ethanol OSR. Evaluation of the catalyst effectiveness against estimated equilibrium compositions. Determination of the most relevant intermediates, coke precursors, and pathways. Comparison of apparent (catalytic) model with elemental (detailed) mechanisms. Abstract: Ethanol is increasingly growing as feedstock for syngas production. In this work, a detailed kinetic mechanism for the oxidative steam reforming (OSR) of ethanol over a Pt-Ni/CeO2 -SiO2 catalyst has been compared against experimental data and apparent kinetics. The rate of production and sensitivity analyses were performed to identify reaction paths, species, and reactions having a significant impact on the distribution of the products. The results have demonstrated that the formation of CH3 CHO, which leads to the CH3 and CO, is due to the hydrogen abstraction forming the CH3 CHOH, whereas the formation of C2 H4, which leads to HCO, CH3, and coke precursors, is related to the pathways forming CH2 CH2 OH. The production of CH2 CH2 OH is successfully hindered by the presence of catalysts, giving a phenomenological reason for the suppression in coke formation. This analysis provides theoretical insights into the kinetic aspects of OSR, aiming at the development of optimized catalysts.